The Relationship between Stress Levels and Fast Food Consumption Behavior and the Incidence of Dysmenorrhea in Adolescent Girls at SMAN 8 Tana Toraja - Lucia Yogyana Suramas; Hayuti Windha Pagiu; Kesia Bawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Cases of Dysmenorrhea (Menstrual pain) during menstruation, especially in young women, are currently common cases. Several theories state that one of the causes of menstrual disorders is stress levels and consumption behavior. So this study aims to determine the relationship between stress levels and fast food consumption behavior with the incidence of dysmenorrhea in young women at SMAN 8 Tana Toraja. Methods: This study uses a quantitative research method with a cross-sectional study. The population in this study were 400 female students of SMAN 8 Tana Toraja with a sample size of 80 female students selected using the stratified random sampling method . Data collection using questionnaires and analyzed with the Chi-Square test . Results: The results of this study indicate that 27.5% of respondents experienced mild stress, 7.2% experienced moderate stress and 66.3 normal, as many as 46.3% of respondents with normal stress levels experienced moderate dysmenorrhea. There are also 88.8% of respondents who consume fast food and only 11.2% of respondents who do not consume fast food. 63.8% of respondents who consume fast food experience moderate dysmenorrhea. The results of the biavariate analysis of Stress Level with Dysmenorrhea Incidence ( p-value = 0.435) and Fast Food Consumption Behavior with Dysmenorrhea Incidence ( p-value = 0.23). Conclusion: in this study there is no relationship between stress levels and fast food consumption behavior with dysmenorrhea in female students of SMAN 8 Tana Toraja.